Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To determine which function has its vertex at the origin, we should convert each function into its vertex form. The general vertex form of a quadratic function is [tex]\( f(x) = a(x - h)^2 + k \)[/tex], where [tex]\((h, k)\)[/tex] is the vertex of the parabola.
Let's analyze each function step by step:
1. [tex]\( f(x) = (x+4)^2 \)[/tex]
This function is already in the vertex form: [tex]\( f(x) = (x - (-4))^2 + 0 \)[/tex].
Hence, the vertex is [tex]\((-4, 0)\)[/tex], which does not lie at the origin.
2. [tex]\( f(x) = x(x-4) \)[/tex]
First, expand the function: [tex]\( f(x) = x^2 - 4x \)[/tex].
To convert this to vertex form, complete the square:
[tex]\[ f(x) = x^2 - 4x = (x^2 - 4x + 4) - 4 = (x - 2)^2 - 4 \][/tex]
So, the vertex form is [tex]\( f(x) = (x - 2)^2 - 4 \)[/tex].
Hence, the vertex is [tex]\((2, -4)\)[/tex], which does not lie at the origin.
3. [tex]\( f(x) = (x-4)(x+4) \)[/tex]
First, expand the function: [tex]\( f(x) = x^2 - 16 \)[/tex].
In vertex form this is written as [tex]\( f(x) = 1(x - 0)^2 - 16 \)[/tex].
Hence, the vertex is [tex]\((0, -16)\)[/tex], which does not lie at the origin.
4. [tex]\( f(x) = -x^2 \)[/tex]
This function is already in vertex form: [tex]\( f(x) = -1(x - 0)^2 + 0 \)[/tex].
So, the vertex is [tex]\((0, 0)\)[/tex], which lies at the origin.
Only the function [tex]\( f(x) = -x^2 \)[/tex] has its vertex at the origin [tex]\((0, 0)\)[/tex].
Therefore, the function that has a vertex at the origin is:
[tex]\[ f(x) = -x^2 \][/tex]
Let's analyze each function step by step:
1. [tex]\( f(x) = (x+4)^2 \)[/tex]
This function is already in the vertex form: [tex]\( f(x) = (x - (-4))^2 + 0 \)[/tex].
Hence, the vertex is [tex]\((-4, 0)\)[/tex], which does not lie at the origin.
2. [tex]\( f(x) = x(x-4) \)[/tex]
First, expand the function: [tex]\( f(x) = x^2 - 4x \)[/tex].
To convert this to vertex form, complete the square:
[tex]\[ f(x) = x^2 - 4x = (x^2 - 4x + 4) - 4 = (x - 2)^2 - 4 \][/tex]
So, the vertex form is [tex]\( f(x) = (x - 2)^2 - 4 \)[/tex].
Hence, the vertex is [tex]\((2, -4)\)[/tex], which does not lie at the origin.
3. [tex]\( f(x) = (x-4)(x+4) \)[/tex]
First, expand the function: [tex]\( f(x) = x^2 - 16 \)[/tex].
In vertex form this is written as [tex]\( f(x) = 1(x - 0)^2 - 16 \)[/tex].
Hence, the vertex is [tex]\((0, -16)\)[/tex], which does not lie at the origin.
4. [tex]\( f(x) = -x^2 \)[/tex]
This function is already in vertex form: [tex]\( f(x) = -1(x - 0)^2 + 0 \)[/tex].
So, the vertex is [tex]\((0, 0)\)[/tex], which lies at the origin.
Only the function [tex]\( f(x) = -x^2 \)[/tex] has its vertex at the origin [tex]\((0, 0)\)[/tex].
Therefore, the function that has a vertex at the origin is:
[tex]\[ f(x) = -x^2 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.